DAMPAK TREND MOBILITAS MASYARAKAT TERHADAP POLUTAN PENCEMAR UDARA SELAMA PSBB PANDEMI COVID-19 - Sylvia Febrina; Yohanna Magdalena Lidya Gultom (HIGIENE: Jurnal Kesehatan Lingkungan, 2023)
This paper examines how the impact of community mobility during COVID-19 large-scale social restriction policy on the concentration of air pollutants (SO2, CO and NO2), where the restriction policy has reduced community mobilization. Using fixed effect panel data regression, it was found that community mobility during restriction policyhad a significant impact on increasing the three pollutants. The daily average concentration of CO and SO2 air pollutants is still above the WHO recommendation limit. This finding shows that despite the restrictions on community activities, there is a mobility pattern that keeps the pollutant concentration high. Keywords: mobility; pollutants; air pollution; environmental; air quality; restriction; covid-19; epidemiology, health